The Nusplingen Plattenkalk – A Shark Lagoon in the Late Jurassic of the Swabian Alb Geopark - Guenter Schweigert; Siegfried Roth (Geoconservation Research)
The Nusplingen Plattenkalk is a Solnhofen-type fossil Konservat-Lagerstaette in the southwestern part of the Swabian Alb, which is scientifically exploited by the Stuttgart Natural History Museum. The Nusplingen Plattenkalk formed in a deep lagoon surrounded by islands. The highly diverse and exceptionally preserved fossil fauna and flora allow a reconstruction of the Late Jurassic marine food-web and the palaeoenvironment. The complete outcrop area is preserved as a national heritage site within the Swabian Alb Geopark. Information for the public is provided by guided tours, a geological trail with a small public sampling site and fossil exhibitions.